TOURISM AND ITS FUNCTION IN THE DEVELOPMENT OF HILLY-MOUNTAINOUS AREAS IN THE MUNICIPALITY RADOVISH - Iliev, Dejan (Macedonian Geographical Society, 2013)
This scientific paper researches issues related to tourism and its function as a generic resource in the development of hilly-mountainous areas in the municipality of Radovish. The scientific work is characterized by its specificity and its own research methodology in which several scientific methods are used: geographic (spatial) method, method of field research, statistical method, method of analysis and synthesis, method of comparison, tabular method etc. The results of this research defines the role of tourism in local economic development and socio-cultural development of village settlements in hilly-mountainous areas in the municipality of Radovish, and tendencies in which direction could be tourism developed as it could affect the development of these areas in the future.
Keywords: tourism, economic development, socio-cultural development